Quality of Nursing Rehabilitation Care (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Study of domestic and foreign experience in planning and organizing the work of the nursing service of the departments of restorative treatment and rehabilitation in the Zangiota hospital-1. Revealing the medical, social and professional personal characteristics of the nursing staff of a multidisciplinary hospital.